Analisis Faktor yang Mempengaruhi Keberlanjutan Usaha Kerajinan Ukir Sanggah di Desa Jehem Kabupaten Bangli - Desak Nyoman Deta Cahyarini,s; M.Rudi Irwansyah (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2026)
This study aimed to identify the factors influencing the sustainability of the ukir sanggah handicraft business in Jehem Village, Bangli Regency, as well as the most dominant factor amid challenges such as the declining number of craftsmen, limited raw materials, and economic pressures. The research employed a quantitative approach, and data were collected through observation, interviews, questionnaires, and documentation. The population consisted of 311 craftsmen, and 76 respondents were selected using the Slovin formula and proportional sampling technique. The data were analysed using the MICMAC method to identify and classify variables based on their levels of influence and dependence within the sustainability system. The results show that business sustainability is influenced by eight interrelated variables, with income emerging as the most dominant factor due to its highest level of influence in both direct and indirect analyses. These findings indicate that the sustainability of the ukir sanggah handicraft business largely depends on economic stability and human resource capacity as the core components of the sustainability system.